First‐Principles Calculations of Lithium‐Ion Migration at a Coherent Grain Boundary in a Cathode Material, LiCoO2. (2nd November 2012) - Moriwake, Hiroki; Kuwabara, Akihide; Fisher, Craig A. J.; Huang, Rong; Hitosugi, Taro; Ikuhara, Yumi H.; Oki, Hideki; Ikuhara, Yuichi
<x xml:space="preserve">Abstract</x> Results of theoretical calculations are reported, examining the effect of a coherent twin boundary on the electrical properties of LiCoO2. This study suggests that internal interfaces in LiCoO2 strongly affect the battery voltage, battery capacity, and power density of this material, which is of particular concern if it is used in all‐solid‐state Li‐ion batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>